Nutritional Changes During Biofortified Maize Fermentation (Steeping) for Ogi Production - Ortiz, Darwin; Nkhata, Smith; Buechler, Aimee; Rocheford, Torbert R.; Ferruzzi, Mario G. (2017)
Maize is a staple food crop with an important role in the household food security in sub-Saharan Africa where a significant number of people suffer vitamin A deficiency. Efforts are underway to develop new maize cultivars with improved levels of pro-vitamin A carotenoids (pVACs). To enhance the bioavailability of nutrients from maize, various processes are used including soaking, fermentation, germination, malting, as well as thermal and mechanical processing. Fermentation is widely used in West Africa in the production of fermented cereal flours and in preparation of porridges and weaning foods. Recovery and bioavailability of pVACs from such foods is not well established for biofortified maize varieties. The purpose of this study was to assess nutritional and physical changes to five promising biofortified maize genotypes during processing of maize to a common fermented food product consumed in West Africa. Composition, stability, carotenoid bioaccessibility and carbohydrate digestibility were evaluated in experimental porridges prepared from each biofortified maize genotype processed with different degrees of fermentation (24, 72, 120h) as traditionally used for “ogi” production. Genotypes evaluated contained 3.0–8.5 μg/g β-carotene equivalents on a dry weight basis (DW). pVAC retention after 24 h and 72 h fermentation ranged from 60–100% among genotypes. However, after 120 h fermentation recovery was reduced 27–48%. These results suggest some variation in stability of pVACs between genotypes. Bioaccessibility of pVACs determined by in vitro digestion of porridges ranged from 1.3–2.3% with significant differences observed among genotypes (p < 0.05) but not fermentation time. Rapid Visco Analyser (RVA) was used to assess functional properties of the fermented flours. RVA data showed that in general fermentation increased final viscosity of the fermented flours from an initial viscosity (403.4 ± 14.3 cP) to a maximum level (722.1 ± 12.2 cP) achieved after 72 h. However, a close relation between genotypes and final viscosity was observed that could potentially impact product sensory characteristics and bioaccessibility of pVACs. Biofortified genotypes did not have differences in their starch digestibility (p > 0.05). However, fermentation time did alter starch digestibility as assessed by glucose release (18.1–19.4 g/100g FW).